Preparation of two kinds of membranes with reverse wettability from waste masks for continuous oil/water separation. Issue 3 (6th February 2023) - Ning, Lianchao; Liu, Yi; Luo, Yang; Han, Yaxin; Zhang, Longfei; Zhang, Ming
Abstract : Resourceful use of waste masks (WMs) has become an important challenge for humanity with the spread of the coronavirus disease (COVID-19). Abstract : Resourceful use of waste masks (WMs) has become an important challenge for humanity with the spread of the coronavirus disease (COVID-19). In this work, WMs were treated by disinfection treatment and then modified via the in situ chemical deposition of SiO2 followed by the grafting of dopamine (DA) and octadecyltrichlorosilane (OTS). By controlling the amount of DA or OTS added, WM-SiO2 /DA (superhydrophilic) and WM-SiO2 /OTS (hydrophobic) membranes were fabricated with reverse wettability with water contact angles of 0° and 147.5°, respectively. The WM-SiO2 /DA and WM-SiO2 /OTS membranes possessed attractive permeability toward water (6793 L m −2 h −1 ) and CCl4 (13 867 L m −2 h −1 ), together with separation efficiencies over 98.0% under gravity. Besides, the WM-SiO2 /DA and WM-SiO2 /OTS membranes were used in a T-shaped device for the analysis of continuous oil/water separation processes. The results showed that oil/water mixtures could be separated continuously regardless of the density of oil/water by virtue of the attractive permeability and separation efficiency. Furthermore, the membranes also demonstrated favorable stability and reusability under harsh operating conditions. Consequently, this work provides an effective and promising way to upcycle waste masks, especially in the field of oil/water separation.